The Maximian Perspective on Paul: A Reconstruction of the “Works of the Law” in Maximus the Confessor - Bergman, Andreas (Verbum Vitae, 2025)
In Paul’s “Works of the Law” in the Perspective of Second-Century Reception, Matthew J. Thomas argues that the “Early Perspective on Paul” (EPP) resembles the New Perspective on Paul (NPP) more closely than the Old Perspective on Paul (OPP). Thomas’ conclusion is based on three questions that he poses to the second-century sources; namely, what the works of the law are, what their purpose is, and why are they not necessary to Christians. This article applies Thomas’ question to the most important exegetical works of one of the greatest Byzantine theologians, Maximus the Confessor, and constructs the “Maximian Perspective on Paul.” Maximus’ perspective on Paul is largely similar to Thomas’ reconstruction of the EPP. Interestingly, however, in contrast to the NPP and the EPP, Maximus’ understanding of the works of the law resembles the OPP, since the “works of the law” can refer to all outward works, not just some of the precepts of the Mosaic law.